Proceedings of the 8th ACM SIGCOMM Conference on Internet Measurement 2008
DOI: 10.1145/1452520.1452557
|View full text |Cite
|
Sign up to set email alerts
|

Traceroute probe method and forward IP path inference

Abstract: Several traceroute probe methods exist, each designed to perform better in a scenario where another fails. This paper examines the effects that the choice of probe method has on the inferred forward IP path by comparing the paths inferred with UDP, ICMP, and TCP-based traceroute methods to (1) a list of routable IP addresses, (2) a list of known routers, and (3) a list of well-known websites. We further compare methods by examining seven months of macroscopic Internet topology data collected by CAIDA's Archipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 20 publications
7
41
0
Order By: Relevance
“…Reference [8], [9] proposes a topology discovery method based on ICMP. This method depends on two basic ICMP tools.…”
Section: Topology Discovery Methods Based On Icmpmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [8], [9] proposes a topology discovery method based on ICMP. This method depends on two basic ICMP tools.…”
Section: Topology Discovery Methods Based On Icmpmentioning
confidence: 99%
“…We cannot rely on ICMP based approach as mentioned in [8] [9] because it works on a higher layer of the TCP/IP Stack and also imposes heavy load on the network infrastructure. Since ICMP is usually used for Denial of Service (DoS) attacks, it is blocked by most network firewalls, which prevent us from determining the structure of the network beyond the firewall.…”
Section: Comparitive Studymentioning
confidence: 99%
“…Since then, traceroute has been extended in order to mitigate its intrinsic limitations. From simple extensions (i.e., the types of probes sent [25,26]) to much more developed modifications. For instance, traceroute has been improved to face load balancing [27] or the reverse path [28].…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, Luckie et al show that there are significant differences in the topology observed following the probing method [24]. ICMP-based traceroute is able to reach more destinations and to collect more evidence of a greater number of AS links (after an IP-to-AS mapping [25][26][27]).…”
Section: Traceroutementioning
confidence: 99%